Perancangan Sistem Informasi Penjualan Dan Stok Opname Berbasis Web Pada Toko Bangunan Kurnia Jaya 2 - Mutiya Anjani; Nabila Maulia; Tasya Andini; Farizi Ilham (Shofanah Media Berkah, 2026)
Kurnia Jaya 2 Building Materials Store is a material shop in Tangerang that has been operating for approximately three years. Daily operations still rely on a manual paper-based system (bon) to record sales transactions, monitor inventory, and manage customer debts, leading to problems such as unmonitored stock, risk of data loss, difficulty retrieving transaction history, and challenges in tracking customer debt accounts and daily profit reports. This study aims to design a web-based sales and stock opname information system through direct observation and interviews with the store owner. The designed system includes features for sales transaction recording via Point of Sale (POS), supplier goods receipt management, real-time stock monitoring with minimum stock notifications using the Min-Max method, barcode scanning, automatic sales reporting, multi-pricing management, and customer debt (bon) management. System design employs UML diagrams including Activity Diagram, Use Case Diagram, Sequence Diagram, and Class Diagram, along with a MySQL database. Functional testing using the Black Box Testing method on 24 Owner/Admin scenarios and 16 Cashier scenarios all yielded Successful results. The system is expected to improve store management efficiency in a structured, accurate manner and support better business decision-making.